2012
DOI: 10.3390/ijerph9114135
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional Study on the Effects of Socioeconomic Factors on Lead Exposure in Children by Gender in Serpong, Indonesia

Abstract: To elucidate the socioeconomic factors influencing lead exposure in elementary school children by gender, 108 children (56 male, 52 female), aged 6–7 years, were randomly selected from 39 elementary state schools in Serpong, Banten, Indonesia. Their parents were interviewed to obtain information on sociodemographic characteristics. Their blood lead (BPb) levels were measured by atomic absorption spectrophotometry. BPb concentrations were significantly higher in males than in females, i.e., 6.8 ± 2.0 (2.9–12.5)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Neuropsychological development is more often impaired in male children than in females [43][44][45]. In addition, we have observed that BPb is higher in male children [50]. Experimental animal studies have also demonstrated sex differences in the effects of lead.…”
Section: During the Course Of Normal Pregnancy Changes In Maternal Bp...mentioning
confidence: 58%
“…Neuropsychological development is more often impaired in male children than in females [43][44][45]. In addition, we have observed that BPb is higher in male children [50]. Experimental animal studies have also demonstrated sex differences in the effects of lead.…”
Section: During the Course Of Normal Pregnancy Changes In Maternal Bp...mentioning
confidence: 58%
“…(2005) showed no statistically significant association between risk of ASD and socioeconomic status [ 85 ]. In addition, children with lower SES have been shown to have more exposure to chemical contaminants [ 86 ] including reported associations with increased blood lead concentrations in children with lower SES [ 87 , 88 ]. In our study, although we observed a significant association between ASD status and SES as well as sociodemographic indicators (maternal age, parental education levels, car ownership by the family, and parish at child’s birth), we did not find a significant association between the blood lead concentrations and the aforementioned SES and sociodemographic indicators.…”
Section: Discussionmentioning
confidence: 99%
“…Pb enters into the body mainly through the respiratory system and the digestive tract, and causes a series of documented adverse effects particularly in the nervous systems [4][5][6], such as developmental delays, insomnia, irritability, tremors, hearing loss, deficits in behavioral functioning, impaired cognitive and learning abilities, and social withdrawal [7][8][9]. Since children have underdeveloped and inadequate blood brain barrier, unrestricted Pb accumulation in the brain will eventually disrupt neural signal transduction and irreversibly damage the nervous system [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%